Antioxidant and electrochemical properties of calcium and lithium ascorbates - Avramchik O. A.; Korotkova E. I. Elena Ivanovna; Plotnikov E. V. Evgeny Vladimirovich; Lukina A. N.; Karbainov Yu. A. Yuri Alexandrovich (2005, 2005)
Title screen